Analysis of Demand Chinese Language Staff and Using on SMEs in Luang Prabang Capital - HOONGSENGPHA, Soudthida; PHOMMACHACK, Thongkhoun; SAYBOUNHEUANG, Saythala; PHANTOUAMATH, Poutthalack (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
This research to analysis of demand for Chinese Language Staff and Using on SMEs in Luang Prabang city. Using by 8 characteristics identified are linguistic proficiency, Communicative, Culture, Content, Citizenship, Attitudes, Vocational and Critical for consider personnel for development of SMEs: this paper is based on the actual opinions of SMEs business who have been recorded in a questionnaire of 400 units and using five level of Likert Scale of questionnaire to collect data, there is a reliability level of 0.904 (90.4%) and Using SPSS 24.0 statistical software for data analyzed by the frequency, percent, mean, standard deviation and one way ANOVA Analysis. The result of the research found that: The SMEs business in Luang Prabang are most of the entrepreneurs are married women, aged between 41-50 years old with bachelor's degree which is a small business in the service sector and has been business between 6-9 years in an individual/family mode. More than half of SMEs business in Luang Prabang do not yet have Chinese language staff. Currently SMEs business in Luang Prabang. At present, SMEs business in Luang Prabang are need of large number of Chinese language staff. In which, a few SMEs business need to improve Chinese language for their staff to increase cooperation and develop the business， both to improve knowledge and to create motivation to work for the staff in the organization. The courses that require more training than others are Chinese language for use in organizations or related organizations with a duration of not more than 1 year by studying together with other organizations or general teaching in the evening/evening of official days taught by Lao teachers and Chinese teachers together. The SMEs business in Luang Prabang need Chinese language staff with 3 main characteristics in 3 aspects are: Chinese language ability, Chinese language communication skills and understanding of Chinese culture. In addition, the results of the hypothesis test also found that: 1) Different types of SMEs in Luang Prabang have different needs for Chinese language staff by: Chinese culture understanding and work attitude. 2) Different Models of SMEs in Luang Prabang have different needs for Chinese language staff by: Creativity and work attitude.